The use of guided writing strategy to improve writing skills among students of ninth year “j” basic general education afternoon session, at colegio de bachillerato “Beatriz Cueva de Ayora”, in the city of loja during the 2020-2021 academic period - Troya Salinas, Jackson Fernando (2021)
The objective of this research was to improve writing skills through the application of guided writing strategy among students of ninth year “J” of basic education afternoon session, at Colegio de Bachillerato Beatriz Cueva de Ayora, in the city of Loja during the 2020-2021 academic period. The methods used in this research work were, the scientific, the descriptive, the statistical and the analytical-synthetic, which allowed to collect, describe, process, analyze and interpret information. The instruments used to gather data on the attitude and performance of learners in writing were field notes, questionnaires, observation sheets and tests, which were applied to twenty students. The results obtained showed that students achieved a satisfactory improvement in the five aspects of writing, which were: vocabulary, spelling, sentence structure, grammar and text organization. In conclusion, through guided writing students showed great interest to be actively involved in writing activities. They constructed texts more accurately and fulfilled their writing tasks more effectively.